PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA JAKARTA ISLAMIC INDEX - Shodiq Purnomo; Sri Yuliati (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
Purpose of research to determine the effect of capital structure, company’s growth and profitability toward corporate value. The determination of the samples is done using purposive sampling method. With determined criteria, there are 30 companies used as the samples. The research used secondary data taken from the performance summary of companies listed in the Jakarta Islamic Index (JII) in the period of 2011 - 2014. The hypothesis testing is done using SPSS. The results of research shows that capital structure and profitability are positive affect and significant to corporate value while a significant negative relation is detected for company's growth.